2012
DOI: 10.1111/j.1349-7006.2012.02332.x
|View full text |Cite
|
Sign up to set email alerts
|

Aurora‐A activation, correlated with hypoxia‐inducible factor‐1α, promotes radiochemoresistance and predicts poor outcome for nasopharyngeal carcinoma

Abstract: Previously, we and others showed that hypoxia-inducible factor-1a (HIF-1a) and transcriptionally upregulated Aurora-A were required for disease progression in several tumors. Here, we address the clinicopathologic value of Aurora-A and HIF-1a in locally advanced nasopharyngeal carcinoma (NPC). Aurora-A and HIF-1a expression was semiquantitatively evaluated by immunohistochemistry staining in 144 cases from a randomized controlled trial. Of these patients, 69 received neoadjuvant chemotherapy plus concurrent ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Previous studies have found that HIF-1α overexpression indicates unfavorable prognosis and may serve as an potential prognostic factor in several cancers (Zhong et al, 1999;Marton et al, 2012;Wan et al, 2012;Li et al, 2013;Luan et al, 2013;Zhang et al, 2013;), including colon, breast , gastric, lung , skin, ovarian, pancreatic, prostate, and renal carcinomas. Furthermore, down-regulated HIF-1α expression in transplanted esophageal squamous cell carcinoma in vivo could enhance the cytotoxicity of cisplatin (Liao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that HIF-1α overexpression indicates unfavorable prognosis and may serve as an potential prognostic factor in several cancers (Zhong et al, 1999;Marton et al, 2012;Wan et al, 2012;Li et al, 2013;Luan et al, 2013;Zhang et al, 2013;), including colon, breast , gastric, lung , skin, ovarian, pancreatic, prostate, and renal carcinomas. Furthermore, down-regulated HIF-1α expression in transplanted esophageal squamous cell carcinoma in vivo could enhance the cytotoxicity of cisplatin (Liao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…All eligible studies were published between 2005 and 2014. All TNM Stages (I-IV) were considered in 18 studies (46.2%) (9,18,20,27,28,30,(34)(35)(36)(37)(38)40,43,44,50,55,56,58), non-metastatic solid tumors (including Stage I-III or localized disease, based solely on singlestage disease or mixture of tumor stages) were considered in 12 (30.8%) studies (22,29,31,33,39,41,42,46,48,51,53,54); metastatic solid tumors (Stage IV) patients were considered in four studies (10.2%) (23,45,49,57); disease stage was not available were considered in five studies (12.8%). Four studies analyzing AURKA mRNA expression used real-time reverse transcription PCR (RT-PCR) (20,34,35,45); one study analyzing AURKA gene amplification by fluorescence in situ hybridization (FISH) (54); the other one used immunohistochemical (IHC) staining and RT-PCR (47); and the remaining 33 studies applied a immunohistochemistry detection method (9,18,19,21-23,27-33, 36-44,46,48-53,55-58).…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…Four studies analyzing AURKA mRNA expression used real-time reverse transcription PCR (RT-PCR) (20,34,35,45); one study analyzing AURKA gene amplification by fluorescence in situ hybridization (FISH) (54); the other one used immunohistochemical (IHC) staining and RT-PCR (47); and the remaining 33 studies applied a immunohistochemistry detection method (9,18,19,21-23,27-33, 36-44,46,48-53,55-58). Eight studies were conducted in patients from European countries (19,21,28,32,36,40,55,57), four in patients from USA (18,20,37,45), three in Oceania countries (33,46,49), one in South America (50), and twenty-three in Asian countries (9,22,23,27,(29)(30)(31)34,35,38,39,(41)(42)(43)(44)47,48,(51)(52)(53)(54)56,58). One or more oncologic outcome parameters were analyzed on multivariate analysis in 33 studies <...>…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…There are more published studies that evaluated pathological hypoxic markers in NPC ( Table 1) (36)(37)(38)(39)(40)(41)(42)(43). Most studies evaluated HIF-1α expression which was found in 32-83% of patients ( Table 1).…”
Section: Evidence Of Hypoxia In Npcmentioning
confidence: 99%